The Effect of Sustainability Report Disclosure, Profitability, Company Size, and Currency Exchange Rate as Moderating Variables on the Company's Stock Price on the Indonesia Stock Exchange (IDX) - Wibisono, Yudo (Jurnal Multidisiplin Indonesia, 2024)
This study examines the effect of sustainability report disclosure, profitability, company size, and currency exchange rates on stock prices in the basic materials, energy, industrial, infrastructure, transportation, & logistics sectors on the IDX for the 2019-2021 period. The goal is to find out how these variables, including the currency rate as a moderation variable, affect stock prices. Factors such as sustainability report disclosure, profitability, and company size are identified as important factors in investment decisions. This research method uses causal type explanatory research that examines the influence of sustainability report disclosure, profitability, company size, and currency exchange rate on stock prices in the basic materials, energy, industrial, infrastructure, transportation & logistics sectors on the IDX. The sample was taken using purposive sampling with a total of 38 companies from 2019-2021. The study concluded that 1) Sustainability report does not have a significant effect on stock prices, 2) Company profitability has a significant effect on stock prices, 3) Company size has a significant effect on stock prices, 4) Currency exchange rates moderate the influence of sustainability reports on stock prices, 5) Currency exchange rates moderate the influence of profitability on stock prices, 6) Currency exchange rates moderate the influence of company size on stock prices stocks in the basic materials, energy, industrial, infrastructure, transportation & logistics sectors on the IDX.